Real‐world effectiveness of repeated ketamine infusions for treatment‐resistant bipolar depression. (26th December 2022) - Fancy, Farhan; Rodrigues, Nelson B.; Di Vincenzo, Joshua D.; Chau, Edmond H.; Sethi, Rickinder; Husain, Muhammad I.; Gill, Hartej; Tabassum, Aniqa; Mckenzie, Andrea; Phan, Lee; McIntyre, Roger S.; Rosenblat, Joshua D.
Abstract: Background: Clinical trials have demonstrated rapid antidepressant effects with intravenous (IV) ketamine for major depressive disorder, with relatively less research specifically for bipolar depression. Herein, we describe the real‐world effectiveness of repeated ketamine infusions for treatment‐resistant bipolar depression. Methods: This study was conducted in a community clinic in Mississauga, Ontario (Canadian Rapid Treatment Centre of Excellence; Braxia Health). In this observational study (NCT04209296), patients with treatment‐resistant bipolar I/II depression ( n  = 66) received four sub‐anesthetic doses of IV ketamine (0.5–0.75 mg/kg) over a two‐week period. Symptoms of depression, suicidality, anxiety, and functioning were assessed with validated self‐report measures. Results: Statistically and clinically significant antidepressant effects were observed in the overall sample, as measured by the Quick Inventory for Depression Symptomatology‐Self Report‐16 (QIDS‐SR16 ) with further reductions in depressive symptoms observed after each subsequent infusion ( n  = 66; mean QIDS‐SR16 reduction of 6.08+/−1.39; p  < 0.0001). Significant reductions of suicidal thoughts (QIDS‐SR16 ‐Suicide Item) and anxiety (Generalized Anxiety Disorder‐7) were also observed with functional improvements on the Sheehan Disability Scale ( p  < 0.0001 on all measures). Moreover, the response rate (QIDS‐SR16 total score decrease ≥50% from baseline) was 35% and remission rate (QIDS‐SR16 total score ≤5) was 20% after four infusions. Infusions were generally well tolerated with treatment‐emergent hypomania observed in only three patients (4.5%) with zero cases of mania or psychosis. Conclusions: Real‐world effectiveness of IV ketamine for bipolar depression was observed. Repeated doses were associated with greater symptom reduction and adequate tolerability.